2018
DOI: 10.4067/s0718-07642018000200089
|View full text |Cite
|
Sign up to set email alerts
|

Visión General, Características y Funcionalidades de la Red Eléctrica Inteligente (Smart Grid)

Abstract: Este artículo presenta una visión general de la red eléctrica inteligente (Smart Grid) con sus características y funcionalidades y se identifica las actividades de investigación, tendencias, problemas y desafíos de la Smart Grid, Para ello se realizó una revisión de la literatura donde se visualiza como la integración de los recursos energéticos distribuidos (generación distribuida y almacenamiento energético), así como los avances de las tecnologías de la información y las comunicaciones, han desarrollado el … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
2
0
4
Order By: Relevance
“…Todo esto se fundamenta en la premisa de asegurar la confiabilidad y continuidad en el suministro eléctrico. (Gómez et al, 2018).…”
Section: Clientes En Relación Con Las Smart Gridsunclassified
“…Todo esto se fundamenta en la premisa de asegurar la confiabilidad y continuidad en el suministro eléctrico. (Gómez et al, 2018).…”
Section: Clientes En Relación Con Las Smart Gridsunclassified
“…Smart grids also known as Smart Grid (SG), emerged as a response to the need to modernize the electric grid, articulating control and monitoring processes with green technologies, also known as non-polluting or environmentally friendly (Gómez et al, 2018). Smart grids are autonomous and improve effectiveness and efficiency in electric power management, allowing utilities to optimize existing infrastructure, minimizing the construction of more power plants (Kobus et al, 2015).…”
Section: Smart Microgridsmentioning
confidence: 99%
“…Likewise, it was found that microgrids currently represent a viable solution for electric power requirements in isolated or non-electrified areas. This new vision of electric energy management has been considered to supply consumption needs in rural areas, according to Gómez et al, (2018) smart grids or Smart Grid propose answers and solutions to the concerns of adequacy of electricity supply. Thus, the incorporation of a basic service such as electricity., allows to substantially improve the living conditions of the population, reduce social inequity, since the electricity supply also has positive effects to improve economic activity at the local level, coupled with the fact that one of the main characteristics of the design of microgrids is that, they behave as small centers of distributed generation to ensure sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…La RVS es un método computacional basado en la teoría de aprendizaje estadístico, que permite realizar aportes a la fiabilidad, la seguridad y la eficiencia de la red eléctrica (Estupiñan et al, 2016;Gómez et al, 2018). Puede resolver el problema de los extremos excesivos y locales, causados por el algoritmo de evolución (Mosquera et al, 2018).…”
Section: Regresión Con Vectores De Soporte -Rvsunclassified